O'QTUVCHI JISMONIY STATUS MAZMUNDAGI JISMONIY RIVOJLANGANLIKGA MANSUB NAZARIY BILIMLAR - A. Abdullaev; Makhmudov Z. B. (Journals Park Publishing, 2022)
The article provides that physical development is one of the indicators of the status of the human body and the Maju of knowledge belonging to its theoretical foundations.
Keywords: Anthropology, workaholism; workaholism; developed lik; morphofunction